StarTalk with Neil DeGrasse Tyson - Neil deGrasse Tyson (National Geographic Society)
In the tradition of Jon Stewart's best-selling EARTH, this beautifully illustrated companion to celebrated scientist Neil deGrasse Tyson's popular podcast and National Geographic Channel TV show is an eye-opening journey for anyone curious about the complexities of our universe.